2008
DOI: 10.1093/nar/gkn688
|View full text |Cite
|
Sign up to set email alerts
|

The Cohesin loading factor NIPBL recruits histone deacetylases to mediate local chromatin modifications

Abstract: Cornelia de Lange Syndrome (CdLS) is a rare congenital malformation disorder. About half of the patients with CdLS carry mutations in the NIPBL gene encoding the NIPBL protein, a subunit of the Cohesin loading complex. Recent studies show association of Cohesin with chromatin-remodeling complexes, either by establishing cohesion or by recruiting Cohesin to specific chromosome locations. In yeast two-hybrid assays, we identified an interaction of NIPBL with the histone deacetylases -1 and -3. These interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…In addition, cohesin/Nipbl may play an active role in gene silencing. A recent study reported the interaction of Nipbl with histone deacetylases, indicative of its role in promoting deacetylation and transcriptional silencing (44). We previously found the binding of cohesin to heterochromatic repeat regions in human cells, which is Nipbldependent but CTCF-independent, also suggesting its link to repressive chromatin organization and gene silencing (15).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, cohesin/Nipbl may play an active role in gene silencing. A recent study reported the interaction of Nipbl with histone deacetylases, indicative of its role in promoting deacetylation and transcriptional silencing (44). We previously found the binding of cohesin to heterochromatic repeat regions in human cells, which is Nipbldependent but CTCF-independent, also suggesting its link to repressive chromatin organization and gene silencing (15).…”
Section: Discussionmentioning
confidence: 83%
“…Key roles for cohesin have been shown in a number of cellular processes including DNA repair, 21,22 chromatin modification, 23 DNA condensation 24 and transcriptional regulation in Drosophila, [25][26][27][28] [36][37][38] have demonstrated that the function of Scc2/NIPBL in sister chromatid cohesion is spatially and temporally associated with that of Scc4/MAU2. The C. elegans homolog mau-2 was originally identified for its role in axon guidance 39 and has subsequently been show to have a role in mitotic chromosome segregation.…”
Section: Cdlsmentioning
confidence: 99%
“…Fission yeast Swi6 is a histone-binding factor required for cohesin association with heterochromatin (Pidoux and Allshire, 2005;Bernard et al, 2001;Nonaka et al, 2002). Intriguingly, the cohesin deposition factor NIPBL (Scc2 in yeast) binds to histone deacetylases in vertebrate cells, potentially linking cohesin deposition to histone modification (Jahnke et al, 2008). The histone deacetylase Sir2 is required for the binding of cohesin to repressed heterochromatin (repressed mating-type loci and rDNA in yeast), although the underlying mechanism appears to involve physical recruitment rather than enzymatic function (Chang et al, 2005;Kobayashi et al, 2004;Wu et al, 2011).…”
Section: A Code For All Processesmentioning
confidence: 99%